THE PROBLEM OF USING ADHESIVES IN THE FIXATION OF COMPLETE DENTURES - Bayramov, Y.I. (World of Medicine and Biology, 2024)
The purpose of the study was to evaluate the functional efficiency of the prosthesis made by traditional and improved methods for the fixation state of the completely removed lamellar prosthesis. In total, the study covered 609 patients aged 45 to 90 years. Evaluation of the functional efficiency showed that subjective opinion of the patient, 33 days after the application of the prosthesis, in the main group among men: 38.1 % – 7 points (excellent), 9.5 % – 6 points (good), 2.4 % – 5 points (satisfactory); among women: 35.7 % – 7 points, 9.5 % – 6 points, 4.8 % – 4 points. In the control group among men: 3.0 % – 7 points, 3.7 % – 6 points, 4.1 % – 5 points, 40.9 % – 0–3 points; among women: 4.3 % – 7 points, 5.7 % – 6 points, 7.1 % – 6 points, 39.6 % – 0–3 points. So, in the improved method, which provides more clearly and accurately fixation, the use of adhesive gel is not required.
Keywords: Secondary complete adentia; complete removable plate prosthesis; orthopedic treatment; prosthetic bed; adhesive gel